Peran manajemen risiko dalam menjaga stabilitas perbankan syariah di tengah ketidakpastian ekonomi - Asy’ari, Hilda Aulia (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the role of risk management in maintaining the stability of Islamic banking amid global economic uncertainty characterized by inflation, market volatility, regulatory changes, and accelerating digital transformation. Islamic banking has distinct characteristics compared to conventional banking because it applies profit-and-loss sharing principles, prohibition of interest, and compliance with Sharia principles, resulting in broader risk complexity. This study employs a qualitative approach using a literature review method by examining various scientific publications, journals, and relevant documents on Islamic banking risk management. The findings indicate that risk management plays a crucial role in identifying, measuring, monitoring, and controlling financing, liquidity, operational, market, reputational, and Sharia compliance risks. Effective implementation of risk management has been proven to reduce non-performing financing, maintain liquidity, improve efficiency, and strengthen banks’ resilience against economic shocks. However, the study also identifies several challenges, including limited human resources, inadequate risk mitigation instruments, and insufficient digital technology readiness. Therefore, risk management strategies should be directed adaptively through governance strengthening, human resource capacity building, technological integration, and regulatory harmonization. Thus, risk management functions not only as a control mechanism but also as a source of competitive advantage and long-term sustainability for Islamic banking institutions.